A utilização de modelos para análise de paisagem na região nordeste do Estado de São Paulo - Paese, Adriana (Universidade Federal de São Carlos, 2002)
This work explores the use of models in landscape analysis. Classification tree models were employed in the identification of potential sites of species occurrence in the Ecological Station of Jataí and Experimental Station of Luiz Antônio, and the mathematical graph was employed in the analyses of a fragmented landscape located in the Northeast region of São Paulo State. The classification tree models used data on primate species occurrence and on environmental variables represented as digital maps in a Geographic Information System. The prediction rules generated by the classification models were projected back on the landscape, locating other places that have the same combination of environmental conditions as those found where the species were firstly observed. By representing the landscape as a mathematical graph, it was possible to simulate the removal of functional connections between habitat patches and the loss of habitat due to land use changes. Habitat patches were classified according to their contribution to species recruitment and landscape connectivity. Although it is considered that additional biological information should be incorporated to the analyses the results of this work may constitute useful guides to prospective field surveys.
Keywords: Ecologia; Ecologia da paisagem; Modelo de classificação por árvore; Sistemas de Informação Geográfica; Grafo matemático; Conectividade da paisagem; CIENCIAS BIOLOGICAS